2015
DOI: 10.1364/oe.23.024013
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of image flicker in a fringe-field switching liquid crystal display by applying a bipolar voltage wave

Abstract: Recently, low-frequency driving of liquid crystal display (LCD) panels to minimize power consumption has drawn much attention. In the case in which an LCD panel is driven by a fringe-field at a low frequency, the image flickering phenomenon occurs when the sign of the applied electric field is reversed. We investigated image flickering induced by the flexoelectric effect in a fringe-field switching (FFS) liquid crystal cell in terms of the transmittance difference between frames and the ripple phenomenon. Expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Consequently, intensive efforts to reduce the power consumption of this mode have been attempted by using the low‐ f driving when static images are being displayed. However, severe issues regarding image quality arise in the low‐ f driving, including image‐flickering owing to flexoelectric effect . The flexoelectric effect is a coupling between elastic deformation and electric polarization of liquid crystals in which the flexoelectric polarization is spontaneously induced by external electric field at a low f .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, intensive efforts to reduce the power consumption of this mode have been attempted by using the low‐ f driving when static images are being displayed. However, severe issues regarding image quality arise in the low‐ f driving, including image‐flickering owing to flexoelectric effect . The flexoelectric effect is a coupling between elastic deformation and electric polarization of liquid crystals in which the flexoelectric polarization is spontaneously induced by external electric field at a low f .…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the image flickering phenomenon, we performed numerical calculation using a commercial simulation program, TechWiz LCD (Sanayi System Co., Korea). We investigated how the electrode spacing affects the image flickering phenomenon, with which we can examine the flexoelectric effect in an LC cell [9][10][11][12]. The LC parameters used for numerical calculations are as follows: the birefringence ǻn = 0.1029, the dielectric anisotropy ǻİ = 7.3, and the elastic constants K 11 = 12.6 pN, K 22 = 5.9 pN, and K 33 = 13 pN.…”
Section: Calculated Resultsmentioning
confidence: 99%
“…Meanwhile, low-frequency driving of a display panel to reduce power consumption, especially in mobile devices, has drawn much attention recently [4í6]. When an FFS LCD panel, the use of which has become a mainstream approach for mobile displays, is driven by a low-frequency electric field, image flicker due to the flexoelectric effect in the LCs can be detected by the naked human eye [7][8][9][10][11].…”
Section: Objective and Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the transmittances of the LCD in the 2 frames are different, and the brightness changes from one frame to the next frame. Previously, some research groups suggested a few methods to reduce the flickering, for example, Oh et al 21 applied a bipolar voltage, instead of a unipolar voltage, to reduce the flexoelectric effect. They also suggested to use redesigned electrode spacing to control the flickering issue.…”
Section: Introductionmentioning
confidence: 99%